Economic burden and healthcare costs of congenital anomalies of the kidney and urinary tract: a systematic review - Alvarino, Akbar Muzakki; Pahlevi, Reza; Situmorang, Gerhard Renaldi; Wahyudi, Irfan; Rodjani, Arry; Raharja, Putu Angga Risky (Medical Journal of Indonesia, 2026)
BACKGROUND Congenital anomalies of the kidney and urinary tract (CAKUT) cause significant morbidity and economic burden worldwide, highlighting the needs to understand its associated costs. This study aimed to assess the economic burden of CAKUT management. METHODS A systematic review was conducted across 5 databases, including PubMed, ScienceDirect, ProQuest, Nature, and Google Scholar, for studies published up to September 11, 2024, focusing on both direct (e.g., hospitalizations, surgeries, and treatments) and indirect (e.g., lost work time and complications management) healthcare costs related to CAKUT and published in English. Non-economic studies, reviews, editorials, abstracts, animal/in vitro studies, and duplicates were excluded. Methodological quality was assessed using the Risk Of Bias In Non-randomized Studies - of Interventions tool. Narrative synthesis and descriptive statistics were applied. Cost-effectiveness analysis followed Joanna Briggs Institute guidelines. RESULTS 8 studies met the inclusion criteria, revealing wide variations in CAKUT-related healthcare costs across countries and interventions. These studies focused on reviewing both direct and indirect costs, along with interventions that reduce overall healthcare expenditure. Key findings include: (1) In the USA, bilateral renal agenesis costs averaged USD 26,032; (2) In Australia, early whole exome sequencing reduced diagnostic costs by 20% in genetic kidney disease cases; (3) Robotic surgery demonstrated long-term cost-effectiveness despite higher inpatient costs; (4) Other cost-saving strategies include the early renal ultrasound algorithm and genomic testing for CAKUT. CONCLUSIONS CAKUT imposes a significant and variable economic burden globally. Identifying cost-effective interventions is crucial for optimizing care and reducing the financial impact. Further research on cost management strategies is needed to improve outcomes and efficiency.